(untitled) (Ameghiniana, 2014)
Four small morphotypes of lycophytes from Lower Carboniferous deposits are described. These remains have been obtained exclusively from one locality and in a single stratigraphic level, west of Jagüé, in the Río Blanco Basin. The material consists of floated lycophytes and has been found as impressions and casts in thinly bedded shales which are occassionaly deformed by dropstones. The flora is principally composed of Archaeosigillaria conferta together with a second Archaeosigillaria species and two still unassigned Iycophytes. This is the first mention of A. conferta for sequences of this region.